Pemberdayaan UMKM Kelurahan Gamer Melalui Digitalisasi Marketing Dalam Program Kuliah Kerja Nyata - Dian Milasari; Duta Bima Saputra; Serly Sairol Millah; Shafa Novidianti; Evita Shania; Arista Sapta Amanda; Galang Zara Sebastian; Anggita Safitri; Nikita Friska Aurelia; Aditya Khairun Nabil; Evrilia Zaza Syarnikova; Hanun Mahdy Muhadzibzib (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2026)
This article describes the introduction of digital marketing to MSME owners in Gamer village. Digital marketing strategy is known as digital marketing, which is a marketing method carried out with the help of digital tools, especially the internet and the various applications it contains and tools that support the use of these media. A marketing method that really makes it easy for sellers and buyers to make online transactions. The method used in this study is qualitative by using the data that has been obtained. The results of this study indicate that there are still many Gamer villagers who do not understand and need knowledge education about digital marketing as a marketing strategy for SMEs.